The special protection in Spain for third parties supporting the forfeiture of illicit assets - Nicolás Rodríguez-García; Omar Gabriel Orsi (Revista Brasileira de Direito Processual Penal)
Spain has developed its legal framework regarding the forfeiture of illicit assets in order to increase efficiency in the prevention and the repression of crimes. To reach that goal, the forfeiture transcends the individual responsible for the crime, reaching third parties in possession of the assets. This quest to reach higher standards of efficiency brings tension between two fundamental principles of the legal framework: on the one hand, to fight crimes efficiently; on the other hand, to preserve due process and property rights. This paper discusses this tension analyzing, in the first section, the legal framework for the forfeiture of assets in possession of third parties unrelated to the crime. The following section focuses on the mandatory intervention of these individuals in the criminal process as a consequence of the asset forfeiture.